CSIR South Africa mobile LIDAR—First scientific results: comparison with satellite, sun photometer and model simulations - M. Tesfaye; W. Alemu; D. Moema; A. Sharma; C. Bollig; G. Mengistu; V. Sivakumar (South African Journal of Science)
We present the first scientific results from the Council for Scientific and Industrial Research - National Laser Centre (CSIR-NLC) mobile LIght Detection And Ranging (LIDAR) and its validation and comparison with other ground-based and space-borne measurements. The LIDAR results are compared with aerosol extinction measurements from the Stratosphere Aerosol Gas Experiment (SAGE) II, optical depth derived from sun photometers employed under the AErosol RObotic NETwork (AERONET) and backscatter coefficients simulated from weather balloon humidity measurements.